The effectiveness of moringa oleifera and musa paradisiaca on hemoglobin levels in postpartum mothers - Viqy Lestaluhu; Meilany Laisouw; Siska Febrina Fauziah; Fadila Fadila; Juhartini Juhartini (Science Midwifery, 2026)
Postpartum anemia is a common maternal health problem that may delay recovery and increase the risk of postpartum complications. Although Moringa oleifera leaves and Musa paradisiaca have individually been reported to improve hemoglobin levels, direct comparative evidence between these locally available food sources remains limited. This study aimed to compare their effectiveness in increasing hemoglobin levels among postpartum mothers.A quasi-experimental pretest–posttest control group study was conducted. Postpartum mothers were allocated into three groups: Moringa oleifera, Musa paradisiaca, and a control group receiving standard postpartum care. Participants in the intervention groups consumed 200 g of the assigned food daily for seven days. Hemoglobin levels were measured before and after the intervention using a digital hemoglobin analyzer. Data were analyzed using paired t-tests, one-way ANOVA, and the Games–Howell post hoc test (p < 0.05). Hemoglobin levels increased significantly in the Moringa oleifera group (9.94 ± 1.63 to 11.40 ± 1.15 g/dL; p = 0.001) and the Musa paradisiaca group (10.84 ± 1.52 to 12.10 ± 1.42 g/dL; p = 0.003), whereas the control group showed no significant improvement (p=0.116). ANOVA demonstrated significant differences in hemoglobin changes among groups (F = 6.938, p=0.003).This study provides novel evidence by directly comparing Moringa oleifera and Musa paradisiaca in postpartum mothers. Both interventions significantly improved hemoglobin levels compared with standard postpartum care, supporting their use as affordable and locally available complementary strategies for managing postpartum anemia.